Reading Between the Signs: Intercultural Communication for Sign Language Interpreters - Holtz, Rolf (Journal of International Students, 2014)
This book presents the subtleties of a most remarkable human attribute: The ability to understand and communicate language. The focus of the book does examine the basic elements of interpreting and translating for the deaf. However, it takes the reader far beyond the linguistic challenges of American Sign Language (ASL) into the realm of interpreting for world cultures. The book presupposes a well-developed understanding of ASL and readers are expected to already be convinced that ASL is a real language. Deaf and hearing individuals will unquestionably profit from the analyses of culture that are always present in the medical, business, educational, and interpersonal situations in which deaf interpreters are active.